Characterization of blaCTX-M Gene in One Klebsiella pneumoniae Isolate from Sick Chickens in China - Gong-zheng HU; Han HU; Bao-guang LIU; Li YUAN; Jian-hua LIU; Yu-shan PAN; Hua WU; Yu-xia CHEN (Journal of Integrative Agriculture)
Two Klebsiella pneumoniae isolates (Kpc1 and Kpc2) were obtained from liver samples of seven dead chickens and identified with Vitek-32 automated identification system. Antimicrobial susceptibilities were determined by the microdilution broth method. Detection of genes encoding class A β-lactamases was performed by PCR amplification, and cloning of the ESBL gene was by plasmid restriction and fragments ligation. Conjugation assay, transformation experiments and plasmid profile analysis were performed. The incompatibility group of ESBL-carrying plasmid was determined by the PCR-based replicon typing method. Lastly, the genetic environment was analysed by direct sequencing of the DNA surrounding the ESBL gene. The genes associated with tetracycline and gentamicin resistance were also sought by PCR. The results revealed that the ESBL phenotype-negative strain Kpc2 only showed resistance to ampicillin, amoxicillin, tetracycline, and doxycycline and carried blaTEM-1 and tet(A) genes. The ESBL-producing strain Kpc1 exhibited multidrug resistant phenotype and harbored blaTEM-1, blaCTX-M-14, tet(A), tet(B), and rmtB genes. K. pneumoniae Kpc1 contained four plasmids with molecular sizes of approximately 59, 6.9, 2.8, and 1.6 kb, but only a 59-kb plasmid, carried blaTEM-1 and blaCTX-M-14 genes, was observed in its transconjugant. The incompatibility group of plasmid carrying blaCTX-M-14 gene could not be determined. The blaCTX-M-14 gene was flanked upstream by an ISEcp1 insertion sequence and downstream by an IS903 element. This work shows that CTX-M-14 is present in K. pneumoniae isolates from chickens in China. The blaCTX-M-14 gene was associated with an upstream ISEcp1 insertion sequence. Our results underline the need for continuous surveillance of the prevalence and evolution of this CTX-M-type β-lactamase in China.